Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I would like to negate the following:

$\exists x, \forall y, \forall z ((F(x,y) \land G(x,z)) \rightarrow H(y,z))$

Would the following proposed solution be correct?

(1) First simplify what is in the brackets - $((F(x,y) \land G(x,z)) \rightarrow H(y,z))$

$(\lnot(F(x,y) \land G(x,z)) \lor H(y,z))$

(2) $\forall x, \exists y, \exists z \lnot ( \lnot(F(x,y) \land G(x,z)) \lor H(y,z)) $

$\equiv \forall x, \exists y, \exists z((F(x,y) \land G(x,z)) \land \lnot H(y,z))$

share|improve this question
1  
Yes, though you’ve done a little more work than necessary. If you remember that $\lnot(\varphi\to\psi)$ is $\varphi\land\lnot\psi$, you can go directly to $$\forall x\exists y\exists z\Big(F(x,y)\land G(x,z)\land\lnot H(y,z)\Big)\;.$$ –  Brian M. Scott Nov 14 '12 at 21:36
    
cheers @BrianM.Scott –  bosra Nov 14 '12 at 21:39

1 Answer 1

up vote 2 down vote accepted

The negation of $P \Rightarrow Q$ is $$\neg(P \Rightarrow Q) \equiv (P \wedge \neg Q)$$ and the negation of "for all" is $$\neg (\forall x)(P(x)) \equiv (\exists x)(\neg P(x)).$$ Similarly, $$\neg (\exists x)(P(x)) \equiv (\forall x)(\neg P(x))$$ so your answer is correct.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.